Вузловий зоб та ендоскопічні втручання: поєднання діагностики та лікування - Грубнік, В. В.; Косован, В. М.; Парфентьєв, Р. С. (Clinical Endocrinology and Endocrine Surgery, 2009)
The article consists of data of investigation and treatment of 109 patients with thyroid nodules. All patients were operated by vide-endoscopic method. In 10 cases thyroid cancer was detected intraoperatively on basis of frozen section. Thyroidectomy was performed vide-endoscopically in 6 patients and with using open technique in 4 patients. At the same time video-endoscopic procedures are minimal traumatic, allow to decrease hospital stay, time of rehabilitation, and in cases of intraoperative detection of cancer it plays the role of differential diagnosis before performing thyroidectomy.